Inventorying authentic teaching materials on Youtube for listening learning plan of Pupuh in elementary school - Dingding Haerudin; Budi Hermawan; R. Ruhaliah; Sutrisna Wibawa; Yatun Romdonah Awaliah; Tri Indri Hardini (Jurnal Cakrawala Pendidikan, 2023)
Our initial observation confirms that authentic teaching materials have not been integrated into teaching Sundanese. With this in mind, the present study aims mainly to describe authentic teaching materials for teaching Sundanese to elementary school students. A descriptive-analytical method with a qualitative approach has been employed as the method in the present research. Data were collected by inventorying authentic teaching materials from YouTube and identifying their relevance to the 2013 Curriculum (Revised edition in 2017). The data obtained is expected to be used as authentic material in the Independent Curriculum. At the time this research was conducted, the Merdeka Curriculum had already begun to be implemented in several driving schools in West Java. The authentic materials we investigated will most likely be compatible to be used as material for project-based learning on Kurikulum Merdeka. The present research has inventoried 17 types of pupuh and found that of 17 pupuh, four have content that is relevant to the teaching theme for elementary school students based on the Curriculum; 3 pupuh, Dangdanggula, Asmarandana, and Gurisa, have content relevant to the theme of second grade Basic Competence, 1 pupuh, Maskumambang pupuh, has content relevant to the theme of third grade Basic Competence. The data were then assessed for their quality based on the criteria for good teaching materials according to the judgment of experts. Selected Sundanese language teachers have been involved in the research to serve as the experts. The results of the quality test reported that the inventoried pupuh is relevant to the Basic Competence as stated in the Curriculum, can motivate students to learn, is practical to use, is useful for students, is interesting to learn, facilitate students to learn, and improves their listening skills and is following the norms prevailing in society.